Selective-path clustered-based routing protocol for large scale wireless sensor networks. (5th May 2020) - Ogundile, Olayinka O.; Oloyede, Muhtahir O.; Osanaiye, Opeyemi A.; Falayi, Elijah O.; Okusanya, Adetokunbo A.
Wireless sensor networks (WSNs) consist of large number of small low-powered electronic sensor devices. Therefore, reliable power saving schemes must be developed in order to manage the energy dissipated and extend the network life and functionality for a meaningful time. Arranging sensor nodes (SNs) into clusters has been viewed as an efficient approach of balancing the energy dissipated in WSNs. Regardless, a clustered WSN needs a robust energy efficient (EE) and energy balanced (EB) routing communication protocol. This paper proposes a selective-path priority table (SPT) EE and EB routing protocol (RP) ideal for most conventional clustering algorithms. The SPT RP forms the priority table by prioritising the k nearest multi-hop paths to the cluster heads (CHs) and/or base station (BS) based on some robust rules. These rules are compiled using a combination of some routing metrics which include the residual energy (RE) and transmission range/power. Firstly, the simulation results indicate that the SPT RP can be combined with most of the conventional clustering algorithm irrespective of the number of deployed SNs. Secondly, the performance of the SPT RP improves as the value of the selected number of routing paths ( k ) increase. More so, the simulation results show that the SPT RP reduces the energy dissipated and can prolong the network life and throughput as compared to related routing schemes.